A new parameter in the diagnosis of acute appendicitis: Ileocolic artery and vein diameter measurements - (:unkn) unknown (My University, 2019)
Aim: To determine the ability of ileocolic artery (ICA) and ileocolic vein (ICV) diameter measurements in the diagnosis of acuteappendicitis.Material and Methods: ICA, ICV, abdominal aorta (AA) and inferior vena cava (IVC) diameters were recorded in 123 patients. Patientswere grouped according to the presence of acute appendicitis clinically-radiologically. The receiver operating characteristic (ROC)curves were constructed to obtain the cutoff values in terms of differentiation of appendicitis and control groups.Results: ICA, ICV, ICA/AA and ICV/IVC measurements differed significantly between the appendicitis (n=75) and control (n=48) groups(p <0.001, p <0.001, p =0.003, p =0.006). The best cutoff values for ICA and ICV to differentiate appendicitis from the control groupwere 2.92 mm and 4.28 mm, respectively. The ICA, with a cut-off point based on the ROC curve, of 2.92 mm provided a sensitivity of70.7%, and a specificity of 70.8%. Applying the cut-off point of 4.28 mm for ICV, generated a sensitivity of 80%, and a specificity of72.9%.Conclusion: Measurements of the ICA and ICV diameter in computed tomography (CT) is a promising application for determiningacute appendicitis. This preliminary study suggests ICA and ICV diameter measurements could contribute as an alternativeparameter to major radiological evidence in the diagnosis of acute appendicitis.
Keywords: Biyoloji; Diş Hekimliği; Alerji; Anatomi ve Morfoloji; Androloji; Anestezi; Odyoloji ve Konuşma-Dil Patolojisi; Biyokimya ve Moleküler Biyoloji; Biyofizik; Biyoteknoloji ve Uygulamalı Mikrobiyoloji; Kalp ve Kalp Damar Sistemi; Hücre Biyolojisi; Klinik Nöroloji; Yoğun Bakım, Tıp; Dermatoloji; Acil Tıp; Endokrinoloji ve Metabolizma; Gastroenteroloji ve Hepatoloji; Geriatri ve Gerontoloji; Sağlık Bilimleri ve Hizmetleri; Hematoloji; İmmünoloji; Enfeksiyon Hastalıkları; Tamamlayıcı ve Entegre Tıp; Tıbbi Etik; Tıbbi İnformatik; Tıbbi Laboratuar Teknolojisi; Genel ve Dahili Tıp; Adli Tıp; Tıbbi Araştırmalar Deneysel; Mikrobiyoloji; Nörolojik Bilimler; Kadın Hastalıkları ve Doğum; Onkoloji; Göz Hastalıkları; Ortopedi; Kulak, Burun, Boğaz; Patoloji; Pediatri; Periferik Damar Hastalıkları; Fizyoloji; Temel Sağlık Hizmetleri; Psikiyatri; Halk ve Çevre Sağlığı; Radyoloji, Nükleer Tıp, Tıbbi Görüntüleme; Rehabilitasyon; Solunum Sistemi; Romatoloji; Spor Bilimleri; Cerrahi; Transplantasyon; Tropik Tıp; Üroloji ve Nefroloji; Farmakoloji ve Eczacılık; Toksikoloji